MAY 2024 PLACEMENT ADS (The Accounting Review, 2024)
Business and Economics Department invites applications for a full-time faculty position (open rank) to begin August 2024.The successful candidate can expect to teach courses primarily in the areas of accounting.The teaching load for the position is 24 credit hours per academic year, normally three courses each semester, along